Assessing Democratic Governance in the Nigerian Fourth Republic, 1999 -2014 - Usman Salisu Ogbo; S. S. Avidime (European Scientific Journal, ESJ, 2016)
The paper assesses democratic governance in the Nigerian fourth republic. Most Nigerians expected the return to democratic governance on May, 29 1999 to set the stage for the socio-economic and political transformation of the country. The paper contends that the democratic experience has been problematic for Nigerians. The paper, underpinned by the elite theory, is descriptive, historical and analytical in nature and employs the secondary source in the gathering of data. The paper argues that the uninterrupted character of the democratic transition, improvement in civil and political rights and some economic development dividends are positive outcome of the democratic experience. Yet, the successes associated with the democratic experience seem to have been overshadowed by poor governance, the problems of poverty, de-industrialization, widespread unemployment, large scale collapse of infrastructure, illiteracy, insecurity of lives and property, political corruption, and weak governance institutions. Consequently, public trust in the democratic process, institutions and actors is in decline. The paper suggests amongst others, responsible and effective political leadership and civil society as critical to a productive democratic performance in Nigeria.